(untitled) (Biodiversitas Journal of Biological Diversity, 2008)
In the present day, medicinal plants increasingly play important role in human health, while about 60-75% of world population depending on plants and their extracts for medication. Selaginella Pal. Beauv. (Selaginellaceae Reichb.) is a potent medicinal plant source. This plant contains biflavonoid compounds, a dimeric form of flavonoids. Flavonoids are secondary metabolite that is most used in medical purposes. They are often occurred in daily consumed vegetables and fruits. Chemical constituents of flavonoids are very diverse, because they are generated in many biosynthetic methods. There are many biflavonoid compounds of Selaginella, i.e. amentoflavone, 2’,8’’-biapigenin, ginkgetin, heveaflavone, hinokiflavone, isocryptomerine, kayaflavone, podocarpusflavone A, robustaflavone, sumaflavone, and taiwaniaflavone. For the plants, these biflavonoid are used to response environmental condition such as defense against pests, diseases, herbivory, and competitions; while for the people, these compounds are used as antioxidant, anti-inflammatory, anti cancer, antimicrobial (antivirus, antibacterial, anti fungal, antiprotozoan), neuroprotective, vasorelaxant, anti UV-irradiation, antispasmodic, anti allergic, antihaemorrhagic, antinociceptive, etc. The antioxidant purpose of biflavonoid is the most important activities of this secondary metabolite. It is related to the anti cancer and anti-inflammatory functions. The antioxidant of biflavonoid is more powerful than Î²-carotene, vitamin C and E. In the future, Selaginella research exhaustively needs to be conducted on morphological and molecular characteristics. It deeply needs to explore on biflavonoid and other natural products constituents, and it also needs to search on their bioactivities. Â© 2008 Jurusan Biologi FMIPA UNS Surakarta Key words: flavonoid, biflavonoid, Selaginella.